FRIENDSHIPS AND SOCIAL RELATIONSHIPS OF PEOPLE LIVING IN RESIDENTIAL AGED CARE. (11th November 2018) - Casey, A S; Low, L; Jeon, Y; Brodaty, H
Abstract: People living in long-term aged care continue to need supportive relationships. Our research used social network analysis methods to explore relationships between people living in a Sydney nursing home. Analyses explored social networks, perceived support/isolation, adult attachment profiles, and staff- and observer-perceptions of multi-valenced relationships. Results indicated few people had friendships, many had no positive relationships, and most felt isolated. Perceptions of isolation and difficulty with relationships may have been influenced by individuals' positions within the larger care-home network and by environmental factors. Network size and quality were correlated with individuals' cognitive-functional ability and attachment style. People wished to reach-out to connect in positive, meaningful ways. However, they applied long-held friendship schema within a dramatically different social context. Observations indicated negative relationships were common and interactions that began positively often ended in rejection and disconnection. Results suggest a pressing need for tailored interventions and a sharper focus on social health.